2007
DOI: 10.1063/1.2817016
|View full text |Cite
|
Sign up to set email alerts
|

Resistive stability of a plasma with runaway electrons

Abstract: In tokamak disruptions the Ohmic current is often replaced by a current of runaway electrons, which is likely to be more peaked in the centre of the discharge than the pre-disruption current. This raises the question of the resistive stability of the post-disruption plasma, where the equilibrium current is entirely carried by the runaway electrons while the cold (∼ 10 eV) background plasma is relatively resistive. It is found that the linear properties of the classical tearing mode are essentially determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(81 citation statements)
references
References 17 publications
(41 reference statements)
8
73
0
Order By: Relevance
“…Whilst the ideal MHD modes are insensitive to the nature of plasma current (Ohmic or RE), the resistive MHD instability in runaway plasmas was investigated in [11]. It was shown that the linear growth rate of the resistive modes in a runaway-dominated plasma is approximately the same as in a plasma without runaways, but with the same current profile.…”
Section: Tokamaksmentioning
confidence: 99%
“…Whilst the ideal MHD modes are insensitive to the nature of plasma current (Ohmic or RE), the resistive MHD instability in runaway plasmas was investigated in [11]. It was shown that the linear growth rate of the resistive modes in a runaway-dominated plasma is approximately the same as in a plasma without runaways, but with the same current profile.…”
Section: Tokamaksmentioning
confidence: 99%
“…31 Previous work found that the linear properties of the classical tearing mode are essentially determined by the thermal plasma, and linear stability is approximately the same as in a plasma without REs but with the same current profile. 32 Unfortunately, internal measurements of the current profile are not possible in these conditions, as the heating beam used for motional stark effect (MSE) measurements fuels the discharge, overwhelms the ohmic heating power, and compromises RE emission measurements. However, no measurable change in internal inductance ( i ) is observed in these plasmas -both on the long time scale of the gradual HXR growth and the prompt time scale of the ECE rise.…”
Section: B Classical Instabilitymentioning
confidence: 99%
“…Here, we introduce a simple modification of the resistive MHD equations, similar to the one used in Ref. [3], to investigate the potential impact of fast electrons on turbulence. In this model, both thermal and fast electrons contribute to the total current.…”
Section: Mhd Modelmentioning
confidence: 99%